2006
DOI: 10.1183/09031936.00108205
|View full text |Cite
|
Sign up to set email alerts
|

Induction chemotherapy, concurrent chemoradiation and surgery for Pancoast tumour

Abstract: The traditional treatment of Pancoast tumour with local approaches (surgery, radiotherapy or a combination of both) leads to a poor outcome due to the high rate of incomplete resection and the lack of systemic control. The aim of the present prospective feasibility study was to determine whether a trimodality approach improves local control and survival.Patients with stage IIB-IIIB Pancoast tumour received induction chemotherapy (three courses of split-dose cisplatin and etoposide or paclitaxel) followed by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 53 publications
1
45
1
1
Order By: Relevance
“…Operative mortality rate ranges from 0% to 6.9% and morbidity from 11% to 47% (25,29,(35)(36)(37)(38)(39)(40)(41)(42)(43). In particular, the SWOG 9416 (35) and JCO 9806 (36) phase II trials showed operative mortality rates of 2.3% and 3% and morbidity rates of 52% and 14%, respectively.…”
Section: Complicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Operative mortality rate ranges from 0% to 6.9% and morbidity from 11% to 47% (25,29,(35)(36)(37)(38)(39)(40)(41)(42)(43). In particular, the SWOG 9416 (35) and JCO 9806 (36) phase II trials showed operative mortality rates of 2.3% and 3% and morbidity rates of 52% and 14%, respectively.…”
Section: Complicationsmentioning
confidence: 99%
“…In particular brachial plexus invasion (59), vertebral body (11,52,53) and great vessels involvements (11,53) are correlated to an higher risk of tumor recurrence. The presence of Horner syndrome at the diagnosis of Pancoast tumor is, equally, a poor prognostic factor (17,54) implying extensive neural involvement; (IV) positive lymph node status, as in NSCLC tumor, is also a significantly poor prognostic factor in Pancoast tumor (17,21,39,(52)(53)(54)(55). In the revised series of Alifano and colleagues (60), the presence of (V) associated major illness and the completeness of resection are the two most important factors affecting the long-term outcome.…”
Section: Prognostic Factors and Relapsesmentioning
confidence: 99%
See 2 more Smart Citations
“…En-bloc resection of the upper lobe, ribs, nerves (brachial plexus) plus or minus vessels is recommended. Many studies published in the past 10 years have established the gold standard in the field as induction therapy consisting of high dose radiotherapy with concurrent cisplatin-based chemotherapy, followed by surgery 4-6 weeks later [124][125][126][127][128][129]. Using this multimodality scheme, perioperative mortality is low and 5-year survival rates are now consistently .40%.…”
Section: Superior Sulcus Tumours (Pancoast Tumours)mentioning
confidence: 96%